A 12-Week Vigorous Exercise Protocol in a Healthy Group of Persons over 65: Study of Physical Function by means of the Senior Fitness Test. (3rd May 2016) - Todde, Francesco; Melis, Franco; Mura, Roberto; Pau, Massimiliano; Fois, Francesco; Magnani, Sara; Ibba, Gianfranco; Crisafulli, Antonio; Tocco, Filippo
Abstract : The aim of this study was to assess the effects of vigorous exercise on functional abilities by means of a Senior Fitness Test (SFT) in a group of elderly adults. Twenty healthy and inactive people performed vigorous exercise (VE: 12 men and 8 women, aged 69.6 ± 3.9 years). At the beginning of the study (T0) and after 3 months (T1), each subject's functional ability was tested for muscular strength, agility, cardiovascular fitness, flexibility, and balance. The VE was designed with continuous and interval exercise involving large muscle activities. Functional exercises were performed between 60% and 84% of heart rate reserve (HRR) for a duration of 65 minutes. Five out of the 6 SFTs performed were found significantly improved: Chair Stand (T0 12.4 ± 2.4, T1 13.5 ± 2.6, p < 0.01 ), Arm Curl (T0 14.2 ± 3.6, T1 16.6 ± 3.6, p < 0.01 ), 2 min step (T0 98.2 ± 15.7, T1 108.9 ± 16.2, p < 0.01 ), Chair Sit-and-Reach (T0 −9.9 ± 7.7 cm, T1 1.7 ± 6.3 cm, p < 0.01 ), and Back Scratch (T0 −15.8 ± 10.9 cm, T1 −8.4 ± 13.1 cm, p < 0.01 ). Our results suggest that a high intensity protocol and functional exercises can improve functional mobility and muscle endurance in those over 65 years of age. SFTs are an effective method for assessing improvements in the functional capacity of elderly adults.